Kebersyukuran dan kesepian pada lansia yang menjadi janda/duda - Resnia Novitasari; Diah Aulia (University of Muhammadiyah Malang, 2019)
Abstrak. Kesepian merupakan permasalahan psikologis yang berdampak negatif bagi perkembangan lansia. Penelitian ini merupakan penelitian survei yang bertujuan untuk menelaah peran dari kebersyukuran terhadap kesepian pada lansia yang telah menjanda dan menduda. Penelitian ini melibatkan 82 orang lansia yang dipilih menggunakan teknik purposive sampling dengan rentang usia 60-90 tahun. Alat ukur yang digunakan dalam penelitian ini adalah Gratitude Questionnaire-Six Item Form (GQ-6) dan UCLA Loneliness Scale (Version 3). Analisis data menggunakan uji korelasi Spearman’s Rho menunjukkan adanya korelasi negatif yang signifikan antara kebersyukuran dan kesepian. Semakin tinggi tingkat kebersyukuran pada lansia maka semakin rendah kesepian yang dirasakan, begitu pula sebaliknya. Dengan demikian, hipotesis dalam penelitian ini diterima.Kata kunci: duda, janda, kebersyukuran, kesepian, lansiaAbstract. Loneliness is one of the psychological issues that impacted negatively on elderly development. This study is a survey study that examines the role of gratitude towards loneliness in the elderly who have been widowed. This study proved 82 elderly people obtained from a purposive sampling technique with the age ranged from 60-90 years. The measuring instrument used in this study is the Gratitude Questionnaire-Six Item Form (GQ-6) and the UCLA Loneliness Scale (Version 3). Data analysis was tested by Spearman’s rho correlation test showed a significant negative correlation between gratitude and loneliness. The higher the gratitude, the lower the loneliness for the elderly, and vice versa. Thus, the hypothesis in this study was accepted.Keywords: gratitude, loneliness, elderly, widowed Abstract. Loneliness is one of the psychological issues that impacted negatively on elderly development. This study is a survey study that examines the role of gratitude towards loneliness in the elderly who have been widowed. This study proved 82 elderly people obtained from a purposive sampling technique with the age ranged from 60-90 years. The measuring instrument used in this study is the Gratitude Questionnaire-Six Item Form (GQ-6) and the UCLA Loneliness Scale (Version 3). Data analysis was tested by Spearman’s rho correlation test showed a significant negative correlation between gratitude and loneliness. The higher the gratitude, the lower the loneliness for the elderly, and vice versa. Thus, the hypothesis in this study was accepted.